Risk Factor of Intra-Uterine Fetal Death in Gaza Governmental Hospitals:Case-Control Study (2018-2019). - ElShanti, Amjad F. H.; EL syed Etewa, Bothyna Bassyoni; Dhair, Ahmed S. H.; Abo Samra, Naema Mohammed Salem (Jour Med Resh and Health Sci, 2020)
The study aimed to find out the factors that cause fetal death in the womb in governmental hospitals in Gaza Strip a controlled study during the period 2018-2019. The study problem was formulated in the following main question: What were the most important factors causing childhood deaths in the womb? The study used descriptive and analytical methods. the study sample was (70) women and (70) controls. For each case, one control was matched. The study found that the average age of cases was (29.60) years compared to (27.1) for controls. The most common maternal risk factors for fetal intrauterine death were parity (24.3%) among cases versus (21.4%) among controls. Medication/substance, congenital anomalies of the fetus, bleeding in the third trimester of pregnancy, prolonged pregnancy after birth, and intrauterine growth retardation are the main risk factors. The study recommended conducting a continuing education program for women and nurses about risk factors for fetal death in the womb.